Reform Options for Mature Defined Benefit Pension Plans the case of the Netherlands - Gerard, Marc (IMF working paper ;, 2019)
The Netherlands has been operating fully funded, defined benefit second pillar pension schemes that have consistently ranked high worldwide for delivering high replacement rates while featuring strong solidarity among members. Yet the long-term sustainability of the Dutch pension funds has been undermined in recent years by protracted low interest rates and unfavorable demographic developments, exacerbating controversies over intergenerational transfer mechanisms within the plans. This has prompted a national debate over ways to move toward more individualization while preserving financial security at retirement for all. This paper draws on this experience, illustrated by stress testing simulations and assessed vis-a-vis solutions implemented in peer countries, to discuss the main policy trade-offs associated with the reform of mature pension systems in advanced economies.